Gold(I)-catalyzed hydroindolylation of allenyl ethers - Kona, Chandrababu Naidu; Shinde, Mahesh H.; Ramana, Chepuri V. (Organic & Biomolecular Chemistry, 2015)
The gold(I)-catalyzed reaction/rearrangement of allenyl ethers has been investigated in the presence of indoles. Either hydroindolylation or alkylation of an indole with the pendant group of allenyl ether has been observed. The reaction outcome seems to be decided mainly by the nature of the pendant group of the allenyl ether. Control experiments are indicative of an inner sphere mechanism for the hydroindolylation reaction.